Lean Six Sigma in healthcare: Fast track surgery for patients undergoing prosthetic hip replacement surgery. Issue 4 (8th May 2019) - Improta, Giovanni; Balato, Giovanni; Ricciardi, Carlo; Russo, Mario Alessandro; Santalucia, Ida; Triassi, Maria; Cesarelli, Mario
Abstract : Purpose: Since healthcare spending accounts for approximately 6.6 per cent of the gross domestic product, reducing waste in health facilities is necessary to generate significant cost savings. After previous work concerning the application of Lean Six Sigma (LSS) to hip surgery, the purpose of this paper is to use LSS as the correct methodology to analyse a clinical pathway. Fast track surgery was introduced to the Complex Operative Unit of Orthopaedic and Traumatology of the University Hospital "Federico II" to improve quality and further reduce costs associated with prosthetic hip replacement surgery. Design/methodology/approach: The DMAIC (Define, measure, analyse, improve, control) roadmap was used as the typical problem-solving approach of the LSS methodology. A rigorous process of defining, measuring, analysing, improving and controlling business problems can be used to reach fixed goals. The paper was written following the Standards for Quality Improvement Reporting Excellence (SQUIRES Guidelines). Findings: In this work, the authors found that multiple variables could influence the length of hospital stay (LOS) for inpatient treatment, thereby increasing patient management costs due to longer periods of hospitalisation. Therefore, LSS analysis of the implemented corrective actions demonstrated the efficacy and efficiency of the novel protocol. The average LOS was reduced from 10.66 to 7.8 days (−26.8 per cent). Originality/value: The introduction of fast track surgery was validated through a rigorous LSS analysis, which demonstrated that the new protocol benefitted both patients and the hospital.